A stitching linear-scan method for roundness measurement of small cylinders. Issue 1 (2018) - Chen, Yuan-Liu; Machida, Yuki; Shimizu, Yuki; Matsukuma, Hiraku; Gao, Wei
Abstract: This paper presents a stitching linear-scan method for roundness measurement of small cylinders. Differing from the conventional rotary-scan method by a roundness measuring instrument which suffers from challenges in accurately aligning a cylinder with the rotational datum axis when the cylinder has a small dimension, the stitching linear-scan method, by which the roundness profile of a small cylinder is obtained by stitching a series of arc profiles around the cylinder circumference linearly scanned by a surface form stylus profilometer, makes it easy in alignment of the small cylinder for roundness measurement. Experiments are presented to demonstrate the stitching linear-scan method.